Coronary Perforation Complicating Percutaneous Coronary Intervention in Patients With a History of Coronary Artery Bypass Surgery: An Analysis of 309 Perforation Cases From the British Cardiovascular Intervention Society Database. (September 2017) - Kinnaird, Tim; Anderson, Richard; Ossei-Gerning, Nick; Cockburn, James; Sirker, Alex; Ludman, Peter; de Belder, Mark; Johnson, Thomas W.; Copt, Samuel; Zaman, Azfar; Mamas, Mamas A.
Abstract : Background—: The evidence base for coronary perforation (CP) occurring during percutaneous coronary intervention in patients with a history of coronary artery bypass surgery (PCI-CABG) is limited and the long-term effects unclear. Using a national PCI database, the incidence, predictors, and outcomes of CP during PCI-CABG were defined. Methods and Results—: Data were analyzed on all PCI-CABG procedures performed in England and Wales between 2005 and 2013. Multivariate logistic regressions and propensity scores were used to identify predictors of CP and its association with outcomes. During the study period, 309 CPs were recorded during 59 644 PCI-CABG procedures with the incidence rising from 0.32% in 2005 to 0.68% in 2013 ( P <0.001 for trend). Independent associates of perforation in native vessels included age, chronic occlusive disease intervention, rotational atherectomy use, number of stents, hypertension, and female sex. In graft PCI, predictors of perforation were history of stroke, New York Heart Association class, and number of stents used. In-hospital clinical complications including Q-wave myocardial infarction (2.9% versus 0.2%; P <0.001), major bleeding (14.0% versus 0.9%; P <0.001), blood transfusion (3.7% versus 0.2%; P <0.001), and death (10.0% versus 1.1%; P <0.001) were more frequent in patients with CP. A continued excess mortality occurred after perforation, with an odds ratio for 12-month mortality of 1.35 for perforation survivors compared with matched nonperforation survivors without a CP ( P <0.0001). Conclusions—: CP is an infrequent event during PCI-CABG but is closely associated with adverse clinical outcomes. A legacy effect of perforation on 12-month mortality was observed. Abstract : Supplemental Digital Content is available in the text.